The uniqueness of meromorphic function shared values with meromorphic solutions of a class of q-difference equations - Zhuo Wang; Weichuan Lin (AIMS Mathematics, 2024)
We first investigate the meromorphic solutions of a class of homogeneous second-order q-difference equations and the uniqueness problem for a meromorphic function with three shared values; then we discuss the uniqueness problem for the meromorphic solutions of a class of nonhomogeneous q-difference equations and a meromorphic function with four shared values.